Modelling of the dilated sagittal sinuses found in multiple sclerosis suggests increased wall stiffness may be a contributing factor - Grant Alexander Bateman; Jeannette Lechner-Scott; Alexander Robert Bateman (Scientific Reports, 2022)
Abstract The cross-sectional area of the superior sagittal sinus (SSS) is larger in multiple sclerosis than normal and correlates with disease severity and progression. The sinus could be enlarged due to a decrease in the pressure difference between the lumen and the subarachnoid space, an increase in wall thickness or increased wall stiffness. The cross-sectional area of the SSS and straight sinus (ST) were measured in 103 patients with multiple sclerosis and compared to 50 controls. The cross-sectional area of the SSS and ST were increased by 20% and 13% compared to the controls (p = 0.005 and 0.02 respectively). The deflection of the wall of the sinus was estimated. The change in pressure gradient, wall thickness or elastic modulus between groups was calculated by modelling the walls as simply supported beams. To account for these findings, the modelling suggests either a 70% reduction in transmural venous pressure or a 2.4 fold increase in SSS wall stiffness plus an 11% increase in wall thickness or a combination of changes. An increase in sinus pressure, although the most straight forward possibility to account for the change in sinus size may exist in only a minority of patients. An increase in sinus wall stiffness and thickness may need further investigation.